THE ROLE OF SCHOOL PRINCIPALS IN DRIVING MGMP AS A MEANS OF PROFESSIONAL DEVELOPMENT OF JUNIOR HIGH SCHOOL TEACHERS - Astuti, Vera; Bedi, Fisman; Fitri, Tin Amalia (Universitas Islam Madura, 2025)
The purpose of this research is to examine the approach of the principal of SMP 2 PGRI Bandar Lampung in advancing MGMP as an effort to professionalize teachers. Education functions as a means of growing character, ethics, as well as mental and physical strength. Teachers play a central role in guiding students to their best potential, and this principle has an important role in fostering teachers' professional growth. The research method used in this study is a qualitative method with the data collection method being interview, observation, and analysis of documentation data, while the data source is the principal and some teachers. The results of this study are that school principals have successfully implemented the MGMP strategy without obstacles, through the provision of facility support, resources, and encouragement of active participation of teachers. In addition, a structured coaching program, teachers are involved in MGMP activities every two months, and are given periodic feedback and evaluations. The principal also connects MGMP activities with curriculum needs, encourages collaboration between teachers, and facilitates access to advanced training. Overall, the strategies implemented are able to create an environment conducive to the development of teachers' competencies, so that they can be active in planning, implementing, and assessing learning. The implication of the research is that schools that want to maximize the role of MGMP in improving the quality of teachers can optimize the MGMP program which is driven by school principals, assisted by teachers and supported by students.